1966
DOI: 10.1042/bj1000190
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the congenitally goitrous sheep. The iodinated compounds of serum, and circulating thyroid-stimulating hormone

Abstract: 1. A group of normal and congenitally goitrous Merino sheep were investigated to identify the metabolic defect present in the abnormal animals. 2. Protein-bound iodine concentrations of serum from goitrous animals (average 5.7mug./100ml.) were higher than normal (average 4.2mug./100ml.; P 0.001), but the hormonal iodine measured as butanol-extractable (131)I was low in the serum of goitrous (average 40.3% of protein-bound (131)I) compared with that of normal (84.2%; P 0.02) sheep. The non-hormonal iodine of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
1

Year Published

1969
1969
2008
2008

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 18 publications
1
7
0
1
Order By: Relevance
“…A similar case in South Australia was reported by Rae et aZ. (1968), the conclusions drawn being similar to those of Falconer (1966aFalconer ( , 1966b). …”
Section: Trapping Defectsupporting
confidence: 87%
See 1 more Smart Citation
“…A similar case in South Australia was reported by Rae et aZ. (1968), the conclusions drawn being similar to those of Falconer (1966aFalconer ( , 1966b). …”
Section: Trapping Defectsupporting
confidence: 87%
“…A biochemical investigation undertaken by Falconer (1966aFalconer ( , 1966b showed that the goitrous animals had higher serum protein-bound iodine 131 levels, but lower butanol-extractable I than normal sheep. The nonhormonal iodine fraction of the goitrous sheep appeared to contain iodotyrosines and iodoprotein.…”
Section: Trapping Defectmentioning
confidence: 99%
“…In spite of this, it appears that most congenital hypothyroidism with deficient Tg is caused by mutations in which intracellular Tg transport is blocked, rather than by defects in the ability to synthesize thyroid hormone per se (1,32). Evolutionary pressure definitely exists for Tg to be maintained as a secreted protein, as its inability to do so (at least in Merino sheep) compromises viability to a stage where animals cannot reach reproductive age (33,34). We now present what we believe to be the first evidence directly implicating the ChEL domain in assisting the intracellular protein transport of Tg.…”
Section: Figurementioning
confidence: 99%
“…introduction Various states of thyroid gland hypofunction result from distinct biochemical abnormalities involving iodide uptake and organification, coupling of iodotyrosines to form iodothyro¬ nines, and de-iodination of iodotyrosines following proteolysis of thyroglobulin (Stanbury & Hedge, 1950;McGirr, Hutchinson & Clement, 1956;Stanbury, Kassenaar & Meijer, 1956;Stanbury & Chapman, 1960). Preliminary studies of congenital goitre in South Australian sheep (Falconer, 1965(Falconer, , 1966aFalconer, Roitt, Seamark & Torrigiani, 1970) have shown these mechanisms to be intact and suggest that the goitre is of a less well-defined type in which abnormal iodoproteins are secreted into the general circulation. The disease has an autosomal recessive mode of inheritance (Mayo & Mulhearn, 1969).…”
mentioning
confidence: 99%
“…The residual absorbance after elution was complete was due to NaSCN. (Falconer, 1965(Falconer, , 1966aMayo & Mulhearn, 1969;Falconer et al 1970) have established that a defect in the biosynthesis of thyroglobulin by the thyroid gland, inherited as an autosomal recessive condition, is the primary cause of congenital goitre in South Australian Merino sheep. Ouchterlony double diffusion in agar revealed iodoproteins resembling sheep albumin and immunoglobulin G in the thyroid glands of sheep with goitre.…”
mentioning
confidence: 99%